The bullwhip effect in supply chains with stochastic lead times - Michna, Zbigniew; Nielsen, Izabela Ewa; Nielsen, Peter (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
In this article we consider a simple two stage supply chain. We quantify the variance amplification of orders – the bullwhip effect in a model with stochastic lead times. Employing the moving average forecasting method for lead time demands we obtain an exact value of the bullwhip effect measure. We analyze the formula using numerical examples.
Mathematical Economics, 2013, Nr 9 (16), s. 71-88
Keywords: supply chain; Bullwhip Effect; inventory policy; stochastic lead time; ead time demand forecasting